Addition of Mineral‐Coated Microparticles to Soluble Interleukin‐1 Receptor Antagonist Injected Subcutaneously Improves and Extends Systemic Interleukin‐1 Inhibition. Issue 7 (23rd August 2018) - Clements, Anna E. B.; Leiferman, Ellen M.; Chamberlain, Connie S.; Vanderby, Ray; Murphy, William L.
Abstract: IL‐1 receptor antagonist (IL‐1Ra) inhibits the pro‐inflammatory activity of IL‐1β. However, its short in vivo half‐life and high dose required to inhibit IL‐1β may limit its use in all but a few clinical scenarios. This study examines whether the addition of mineral‐coated microparticles (MPs) to a solution of IL‐1Ra extends its ability to inhibit IL‐1β activity when administered as a subcutaneous injection. MPs efficiently bind proteins in solution and provide sustained protein delivery. In vitro assays demonstrate that IL‐1Ra released from MPs is biologically active and inhibits IL‐1β activity. When MPs are added to an IL‐1Ra solution and injected subcutaneously into a murine model, serum IL‐1Ra is elevated for a longer duration compared to the treatment with the IL‐1Ra solution alone. Further, the addition of MPs to the IL‐1Ra solution results in the inhibition of IL‐1β activity for 7 days. A novel MP formulation that layered IL‐1Ra throughout the coating extends inhibition of IL‐1β activity in vivo for at least 14 days, suggesting potential for long‐term IL‐1β inhibition. Overall addition of MPs to an IL‐1Ra solution injected subcutaneously prolongs the duration of elevated serum concentration of IL‐1Ra and extends its ability to inhibit IL‐1β activity. Abstract : The addition of mineral‐coated microparticles to interleukin‐1 receptor antagonist (IL‐1Ra) extends the inhibition of interleukin‐1 activity after a single subcutaneous administration. Mineral‐coated microparticles have a high loading capacity and release IL‐1Ra in a sustained manner. The serum concentration of IL‐1Ra is elevated and IL‐1 activity is inhibited for a longer duration with the addition of mineral‐coated microparticles.